A SQP based on an interior-point strategy for nonlinear inequality constrained optimization problems - Costa, M. Fernanda P. (2005)
This paper describes a sequential quadratic programming (SQP) algorithm for solving nonlinear inequality constrained optimization problems. The QP subproblems are solved by a primal-dual interior-point method that uses a variant of the Mehrotra's predictor-corrector algorithm. Preliminary numerical testing indicates that the method is effective.